Pharmacological potential of Baccharis dracunculifolia in the treatment of osteoarthritis - Costa, Elisabete Apolinário da (2017)
Baccharis dracunculifolia D.C. (Asteraceae) (Bd) is a medicinal Brazilian shrub, popularly known as "alecrim do campo" and "vassoura", known for its antioxidant, anti-inflammatory, anti-stress and other activities. Antioxidants are substances that prevent various pathological changes in living cells and medicinal plants are considered potential sources of natural antioxidants. Inflammation is a protective reaction that is triggered by stimuli in response to tissue infections and injuries, however dermal inflammation can cause acute and chronic diseases depending on the time of persistence. Osteoarthritis (OA) is the most common form of arthritis and the most debilitating, affecting about 40 million people in Europe, especially the elderly. OA is characterized by progressive degeneration of tissues within and surrounding the joints and by recurrent inflammatory episodes that lead to structural changes, including cartilage erosion, fibrillation and decreased thickness of articular cartilage. In this work, experimental OA was induced in a group of 8 week old female ovariectomized rats (Rattus norvegicus, var. Albinus, Wistar), weighting 210 ± 17 g. Animals were divided in 4 groups (n = 6 per group): (i) SHAM, (ii) ARTH, (iii) ARTH treated with Bd extract (50 mg/kg), and (iv) ARTH treated with Bd extract (100 mg/kg). Four weeks after induction of OA in the animals, Bd extracts were administrated by gavage for a successive period of 5 week. Throughout this period, the animals were assessed for changes in gait (catwalk test), hyperalgesia in the joints (PAM), locomotor ability (OFT), knee circumference, and acute dermal inflammation. The results of this study showed that B. dracunculifolia possesses phenolic compounds and antioxidant and anti-inflammatory activity. Treatments with B. dracunculifolia improved motor performance, especially in the group treated with 100 mg/kg of Bd extract. Otherwise, treatment with 50 mg/kg of Bd extract reduced mechanical hyperalgesia. The histology of the joints shows that the treatments with extract of Bd, mainly the treatment of Bd100, inhibit the wear of the cartilage in the joints. In addition, dermal inflammation was also resolved with the topical treatment of B. dracunculifolia. This dissertation should be seen as an aid to the development of new natural drugs, mainly for the treatment of osteoarthritis and its additional consequences to the disease, as well as for dermal inflammations. However, more studies will be needed.